A Case Study of Examination Malpractice Terminated Through Counselling (21-Year-Old Undergraduate Male) - Kennedy, Margaret George (Advances in Social Sciences Research Journal, 2024)
The goal of counseling is to get the client better than he/she came for counselling. The aim of this case study is to share the experiences of Owunari (21-year old undergraduate male) who was invited for counselling by the counsellor on account of an alleged involvement in examination malpractice (within ethical limits). The client came for counselling because he was invited by the counsellor. Owunari did not deny the allegation, he confessed that it has been his trade in stock since his second year as he goes about doing menial jobs to finance his education after the demise of his sponsor. Counsellor with the consent of the client mapped out a weekly schedule of meeting, the goal was to have a better understanding of the client’s problem with a view to helping him overcome it. Six sessions of Counselling were held with the client during which active listening and responsiveness, empathy, questioning and directive counselling were explored to help the client to learn how to solve his problem. The counsellor did a background check on him from classmates and associates and confirmed all his claims. Counsellor provided immediate help by providing upkeep, and payed the balance of his fees, she gave him several links to seek for sponsorship. One of the links yielded dividend as George Mangibo reach out foundation offered him a full scholarship to complete his education. At this point counselling was terminated and examination malpractice jettisoned.